1995
DOI: 10.1006/viro.1995.1352
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 in the Developing CNS: Developmental Differences in Gene Expression

Abstract: HIV-1 infection of the CNS plays a direct role in the pathogenesis of AIDS dementia that frequently accompanies systemic AIDS. Both adult and pediatric AIDS are characterized by a high proportion of CNS disease. However, the pathogenic mechanisms responsible for AIDS dementia are not understood. A transgenic mouse model using the LTRs of two CNS-derived strains of HIV-1 (HIV-1JR-CSF and HIV-1JR-FL) has been developed to study HIV-1 gene expression in vivo. Analyses of expression in adult transgenic mice reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that B elements within the HIV-LTR promoter are sensitive to neuronal NF-B activity in vitro (Rattner et al, 1993) and in vivo (Corboy et al, 1992;Buzy et al, 1995). To produce a reporter construct that would reflect endogenous NF-B activity in neurons, we generated an NF-B responsive minigene containing three tandem HIV-derived B binding element repeats placed proximal to a minimal promoter derived from SV40.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that B elements within the HIV-LTR promoter are sensitive to neuronal NF-B activity in vitro (Rattner et al, 1993) and in vivo (Corboy et al, 1992;Buzy et al, 1995). To produce a reporter construct that would reflect endogenous NF-B activity in neurons, we generated an NF-B responsive minigene containing three tandem HIV-derived B binding element repeats placed proximal to a minimal promoter derived from SV40.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Kaposi's sarcoma and AIDS dementia complex are complications that are secondary to cofactors (human herpesvirus 8) or a consequence of a more direct viral effect (tropism for the central nervous system [CNS]) (38)(39)(40). The pathological basis for the development of renal disease has been enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Ray and coworkers has provided evidence that not only do renal cells become infected, but HIVAN patients appear to have viral isolates that have adapted to replication in renal cells (12). The evolution of HIV-1 strains with altered tropism has precedence in AIDS dementia (39,40). AIDS patients with dementia complex have macrophage tropic strains of HIV-1 that have adapted to replication in microglial cells through mutations in envelope as well as the LTR, allowing for viral gene expression in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Besides differences in envelope sequences of the virus that influence the occurrence of nervous system disease (9), the LTR region is also able to contribute to HIV-1 cell type-specific expression. This was demonstrated by transgenic mouse studies which revealed that the LTR of neurotropic HIV-1 strains JR-FL and JR-CSF directs gene expression in CNS neurons (10,11); in contrast, the lymphotropic LAI strain was unable to direct gene expression in the CNS of transgenic mice (12,13). These transgenic data strongly suggest the importance of cellular transcription factors present in brain cells, different from those in non neural cells.…”
mentioning
confidence: 96%